Redox Imbalance and Its Metabolic Consequences in Tick-Borne Diseases - Groth, Monika; Skrzydlewska, Elżbieta; Dobrzyńska, Marta; Pancewicz, Sławomir; Moniuszko-Malinowska, Anna (Frontiers in Cellular and Infection Microbiology, 2022)
One of the growing global health problems are vector-borne diseases, including tick-borne diseases. The most common tick-borne diseases include Lyme disease, tick-borne encephalitis, human granulocytic anaplasmosis, and babesiosis. Taking into account the metabolic effects in the patient's body, tick-borne diseases are a significant problem from an epidemiological and clinical point of view. Inflammation and oxidative stress are key elements in the pathogenesis of infectious diseases, including tick-borne diseases. In consequence, this leads to oxidative modifications of the structure and function of phospholipids and proteins and results in qualitative and quantitative changes at the level of lipid mediators arising in both ROS and ROS enzyme-dependent reactions. These types of metabolic modifications affect the functioning of the cells and the host organism. Therefore, links between the severity of the disease state and redox imbalance and the level of phospholipid metabolites are being searched, hoping to find unambiguous diagnostic biomarkers. The molecular effects of oxidative stress are also assessed in the context of the effective pharmacotherapy of tick-borne diseases.